Role of Osteoarthritis, Comorbidity, and Pain in Determining Functional Limitations in Older Populations: European Project on Osteoarthritis. Issue 6 (26th May 2016) - Zambon, Sabina; Siviero, Paola; Denkinger, Michael; Limongi, Federica; Victoria Castell, Maria; van der Pas, Suzan; Otero, Ángel; Edwards, Mark H.; Peter, Richard; Pedersen, Nancy L.; Sánchez‐Martinez, Mercedes; Dennison, Elaine M.; et al.
Abstract : Objective: To evaluate the role of comorbidity and pain in the association between hip/knee osteoarthritis (OA) with self‐reported as well as performance‐based functional limitations in a general elderly population. Methods: We analyzed the data of 2, 942 individuals, ages between 65 and 85 years, who participated in the European Project on Osteoarthritis, which was made up of 6 European cohorts (from Germany, Italy, The Netherlands, Spain, Sweden, and the UK). Outcomes included self‐reported physical function measured by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and the participants' performance‐based physical function was evaluated using the walking test. Results: While comorbidity did not affect the significant association between hip/knee OA and physical function limitations found in the participants, pain reduced the effect of OA on self‐reported physical function, and it cancelled the effect of OA on the walking test. Obesity, anxiety, depression, and cardiovascular diseases were associated with the worst WOMAC scores. Obesity, cognitive impairment, depression, peripheral artery disease, and stroke were associated with the worst walking times. Conclusion: These findings demonstrate that while comorbidity is strongly and independently associated with functional limitations, it does not affect the OA–physical function association. Hip/knee OA is associated with self‐reported impairment in physical function, which was only partially mediated by pain. Its association with physical function, as evaluated by the walking test, was instead completely mediated by pain.